Night-time decline in plant respiration is consistent with substrate depletion - Simon Jones; Lina M. Mercado; Dan Bruhn; Nina Raoult; Peter M. Cox (Communications Earth & Environment, 2024)
Abstract Understanding the response of plant respiration to climate change is key to determining whether the global land carbon sink continues into the future or declines. Most global vegetation models use a classical growth-maintenance approach, which predicts that nocturnal plant respiration is controlled by temperature only. However, recently published observations of plant respiration show a decline through the night even at constant temperature, which these global models cannot reproduce. Here we assess the role of respiratory substrates in this observed decline by evaluating an alternative model of plant respiration, in which the rate of respiration at constant temperature is instead dependent on the size of available substrate pools. We find that the observed decline in nocturnal respiration is reproduced by a model with just two substrate pools, one fast and one slow. These results demonstrate a need to change the way that plant respiration is represented in global vegetation models, moving to models based on labile pools which represent only a fraction of total plant biomass. These models naturally represent plant acclimation via changing pool-sizes and may have a significant impact on the long-term predictions of the global land carbon sink.